Can someone help me figure this out? I got confused on couple of steps..
we are asked to find Z
here is the solution where i got confused
x^2-x/y^2=z ( i got lost here. it looks like we multiplied by x to get rid of denominator but where did we get y^2 from?
x^2 y/y^2 - x/y^2=z ( again i got lost here)
can someone help me understand this little bit better. I would really appreciate it
2) get rid of x------->X^2-X/Y=YZ
3) get rid of y------->X^2.Y-X=Y^2.Z
4) devide both sides by Y^2------> (X^2.Y-X)/Y^2=Z
5) take X out of paranthesis-------> X(XY-1)/Y^2=Z, thus z= x(xy-1)/y^2